The phonology of Japanese - Labrune, Laurence (Oxford : Oxford University Press, 2012)
This account of the phonology of Japanese and its major dialects presents original analyses of every aspect of the Japanese sound system, including its segment inventory, prosodic units, mora and syllable, prosody, and accent.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Japanese language -- Phonology